2020
DOI: 10.1002/pbc.28857
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in pediatric survivors of childhood cancer and hematopoietic cell transplantation from a single center in New York City

Abstract: Childhood cancer survivors are at increased risk for treatment-related late effects; data are lacking on how coronavirus disease 2019 (COVID-19) infection impacts this cohort. We assessed COVID-19-related symptoms, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) IgG seroprevalence, and rate of COVID-19-related hospitalization among 321 asymptomatic survivors of childhood cancer or transplantation seen for routine long-term follow-up between May and September 2020 in a New York City tertiary cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…While only four (4.5%) CCS in this cohort had COVID infection, it is likely that a far higher number have tested positive subsequently. The presentation of COVID was mild, as reported elsewhere [ 25 ].…”
Section: Discussionsupporting
confidence: 58%
“…While only four (4.5%) CCS in this cohort had COVID infection, it is likely that a far higher number have tested positive subsequently. The presentation of COVID was mild, as reported elsewhere [ 25 ].…”
Section: Discussionsupporting
confidence: 58%
“…One study from a single institution in New York found that among 321 survivors seen over a 4-month period in their long-term follow-up clinic and assessed for COVID-19 symptoms or history, five (1.6%) reported a previous PCR-confirmed SARS-CoV-2 infection, one of whom required hospitalization. 25 A previous population-based study in Ontario found no increased risk of SARS-CoV-2 infection among survivors of childhood cancer, but did not evaluate postinfection complications or vaccine uptake patterns. 26 Consequently, there remains significant uncertainty about whether young survivors may experience more substantial morbidity related to SAS-CoV-2 than the general population.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies from different countries have also reported surveillance through the molecular detection of SARS-CoV-2 and the seroprevalence of anti-SARS-CoV-2 antibodies in healthcare professionals and patients in general hospitals [28][29][30] and cancer centers 18,22,[31][32][33] . However, only one pediatric study 23 evaluated the seroprevalence in patients undergoing HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hematologic malignancies, including HSCT recipients, have an increased risk of severe outcomes and mortality from COVID-19, as several studies have shown [15][16][17][18][19][20][21] and, as far as we know, only one study has reported the surveillance (only seroprevalence) for COVID-19 in pediatric HSCT recipients 22 . Therefore, our study is among the first to evaluate the surveillance for COVID-19 in the specific setting of an HSCT service, including adult patients ( ≥ 18 years old) and HCW, using the molecular identification of SARS-CoV-2 in saliva and plasma, as well as the seroprevalence of anti-SARS-CoV-2 IgG.…”
Section: Introductionmentioning
confidence: 99%